Architectural encounters with essence and form in modern China - Rowe, Peter G. (MIT Press, 2002)
"Built around snatches of discussion overheard in a Beijing design studio, this book explores attitudes toward architecture in China since the opening of the Treaty Ports in the 1840s. Central to the discussion are the concepts of ti and yong, or "essence" and "form," Chinese characters that are used to define the proper arrangement of what should be considered modern and essentially Chinese. Ti and yong have gone through various transformations - for example, from "Chinese learning for essential principles and Western learning for practical application" to "socialist essence and cultural form" and an almost complete reversal to "modern essence and Chinese form.""--Jacket